PROGRAM KERJA PAGAR BARU (PENDAMPINGAN KELUARGA SIAGA TUBERKULOSIS PARU - Mohammad Lutfi; Mulia Mayangsari (STIKES NGUDIA HUSADA MADURA, 2022)
Pulmonary TB disease suffered by individuals in their lives will have a negative impact, both physically, mentally and socially. TB also has other negative impacts, socially stigmatized and even ostracized by the community. According to Miller (2018), rejection and shame often prevent people from seeking treatment and completing treatment. So far, the implementation of care, treatment and prevention of TB transmission is mostly done to the sufferer himself. The patient must be responsible for all his care and treatment for his recovery. The involvement of family members is still not optimal or only as PMO (Drug Swallowing Supervisor). Based on the results of the study that was carried out on 15-17 June 2022 in Bajeman Village, it was found that he had TB (Tuberculosis). Therefore, the new fence work program (assistance for pulmonary tuberculosis standby families) is expected to be a program for the advancement of health in Bajeman Village. This community service In general, this activity aims to create families and TB sufferers who can prevent and reduce TB disease so as to reduce the death rate due to TB and others. With this activity, it is hoped that people at risk of TB will know about TB disease, how it is transmitted, its treatment and prevention